Empowerment and feminine discourse: the case of Queen Letizia of Spain - Peña Jiménez, Palma (Estudios sobre el Mensaje Periodístico, 2019)
Feminisim has gained an unusual strength in the last years and so has the women collective, which has accomplished some evident achievements. The Queen Letizia, has certainly not been oblivious to this fact, always refering to the struggle for equality in her public appereances, as well as sexual harassment and domestic violence. This fact turns out to be relevant as it is not usual for a Queen to take part in such speeches and specially with that level of succintness and commitment.This work is about the contents of Queen Letizia’s public speeches and their broadcasting itself. We also study the degree of involvement t hat she acquires with her words, with a special focus on women rights related issues.